2018
DOI: 10.1111/nph.15500
|View full text |Cite
|
Sign up to set email alerts
|

In vivo phosphoenolpyruvate carboxylase activity is controlled by CO2 and O2 mole fractions and represents a major flux at high photorespiration rates

Abstract: Summary Phosphenolpyruvate carboxylase (PEPC)‐catalysed fixation of bicarbonate to C4 acids is commonly believed to represent a rather small flux in illuminated leaves. In addition, its potential variation with O2 and CO2 is not documented and thus is usually neglected in gas‐exchange studies. Here, we used quantitative NMR analysis of sunflower leaves labelled with 13CO2 (99% 13C) under controlled conditions and measured the amount of 13C found in the four C‐atom positions in malate, the major product of PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…Recently, a potential role for PEPC in C 3 plant metabolism at high photorespiratory (low CO 2 /high O 2 ) conditions has been proposed (Abadie and Tcherkez, 2019; Tcherkez and Limami, 2019). Here we also found that PPC2 is involved in seedling development by modulation of photorespiratory metabolism at low CO 2 conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a potential role for PEPC in C 3 plant metabolism at high photorespiratory (low CO 2 /high O 2 ) conditions has been proposed (Abadie and Tcherkez, 2019; Tcherkez and Limami, 2019). Here we also found that PPC2 is involved in seedling development by modulation of photorespiratory metabolism at low CO 2 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in sunflower have shown that the malate content closely correlates with photorespiration by metabonomics analyses and C 3 PEPC fixation increased at high photorespiratory condition (low CO 2 or high O 2 ) (Abadie et al , 2017; Abadie and Tcherkez, 2019), indicating non-photosynthetic PEPC may still contribute to photorespiration in C 3 plant. The studies in Arabidopsis have reported the novel function of C 3 PEPC in regulating the balance of carbon/nitrogen metabolism (Masumoto et al , 2010; Shi et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are ignored here as fractions of these components in R d are generally unknown. There may also be some activity of phosphoenolpyruvate carboxylase (V pepc ) in cytosol (Douthe et al 2012;Abadie and Tcherkez 2019), which would counteract the effect of (F + R d ) on g m,app . But our procedure of estimating R d may have accounted for this, i.e.…”
Section: Analysing Mesophyll Resistancementioning
confidence: 99%
“…1 H-NMR analyses of absolute metabolite content were carried out on leaf extracts (10% D 2 O) done with 21 mg lyophilized sample in powder extracted with 1 ml phosphate buffer pH 7 (15 mM), using a 700 MHz NMR spectrometer (Bruker Advance III) with water suppression by excitation sculpting. 13 C-NMR analyses were carried out on leaf extracts with EDTA (12.5 mM) and maleate (standard; 125 µmol per sample) over 12 500 scans as in Abadie & Tcherkez (2019). Metabolic fluxes were estimated using a set of differential equations implemented across four steps of 1200 time increments, as in Cui et al (2020).…”
Section: Nmr Analyses and Flux Calculationsmentioning
confidence: 99%